Predicting remaining life of lattice steel transmission tower based on condition assessment and corrosion hazard data - Usman F.; Khalid N.H.N. (EDP Sciences, 2023)
This paper presents a novel approach for predicting the remaining life of lattice steel transmission towers in Malaysia. The transmission tower components assessment grouped into ground corrosive condition, foundation condition, lattice steel body of the tower, and conductor. Significant and scientific field investigation and visual assessment evaluate the state of the tower. The corrosion hazard, which is a product of climate and air pollution data, is used. Three separated lines and 84 towers were selected with different ages of the tower in service. The Weighing Scoring Method with Analytical Hierarchy Process to impose the weighed factor was used. The survival function analysis is used to predict service life, and the tower remaining life was determined. The paper shows how to use the model to predict the remaining life of a transmission tower and how this can be used to advise maintenance planning. The Authors, published by EDP Sciences.